The ASEAN intergovernmental commission on human rights : institutionalizing human rights in Southeast Asia - Tan, Hsien-Li , 1979- (Cambridge University Press, 2011)
"This assessment of progress in Southeast Asia on human rights begins in the wake of the ?Asian values? debate and culminates in the formal regional institutionalisation of the ASEAN Intergovernmental Commission on Human Rights (AICHR). Chapters examine the arduous negotiation of AICHR, the evolving relationship between ASEAN states? and the international human rights system, and the historical and experiential reasons for hesitancy. The text concludes with a discussion of how the evolving right to development impacts upon AICHR and international human rights in general, and how their preference for economic, social and development rights could help ASEAN states shape the debate"-- Provided by publisher.